Parallel Aspects of the Microenvironment in Cancer and Autoimmune Disease. (22nd February 2016) - Rahat, Michal A.; Shakya, Jivan
Abstract : Cancer and autoimmune diseases are fundamentally different pathological conditions. In cancer, the immune response is suppressed and unable to eradicate the transformed self-cells, while in autoimmune diseases it is hyperactivated against a self-antigen, leading to tissue injury. Yet, mechanistically, similarities in the triggering of the immune responses can be observed. In this review, we highlight some parallel aspects of the microenvironment in cancer and autoimmune diseases, especially hypoxia, and the role of macrophages, neutrophils, and their interaction. Macrophages, owing to their plastic mode of activation, can generate a pro- or antitumoral microenvironment. Similarly, in autoimmune diseases, macrophages tip the Th1/Th2 balance via various effector cytokines. The contribution of neutrophils, an additional plastic innate immune cell population, to the microenvironment and disease progression is recently gaining more prominence in both cancer and autoimmune diseases, as they can secrete cytokines, chemokines, and reactive oxygen species (ROS), as well as acquire an enhanced ability to produce neutrophil extracellular traps (NETs) that are now considered important initiators of autoimmune diseases. Understanding the contribution of macrophages and neutrophils to the cancerous or autoimmune microenvironment, as well as the role their interaction and cooperation play, may help identify new targets and improve therapeutic strategies.